Association of Shoot and Root Responses to Water Deficit in Young Faba Bean (Vicia faba L.) Plants - Belachew, Kiflemariam Y.; Nagel, Kerstin A.; Poorter, Hendrik; Stoddard, Frederick L. (Frontiers in Plant Science, 2019)
Water deficit may occur at any stage of plant growth, with any intensity and duration. Phenotypic acclimation and the mechanism of adaptation vary with the evolutionary background of germplasm accessions and their stage of growth. Faba bean is considered sensitive to various kinds of drought. Hence, we conducted a greenhouse experiment in rhizotrons under contrasting watering regimes to explore shoot and root traits and drought avoidance mechanisms in young faba bean plants. Eight accessions were investigated for shoot and root morphological and physiological responses in two watering conditions with 4 replications. Pre-germinated seedlings were transplanted into rhizotron boxes filled with either air-dried or moist peat. The water-limited plants received 50 ml water at transplanting and another 50 ml water four days later, then no water was given until the end of the experimental period, 24 days after transplanting. The well watered plants received 100 ml of water every 12 hours throughout the experimental period. Root, stem and leaf dry mass, their mass fractions, their dry matter contents, apparent specific root length and density, stomatal conductance, SPAD value and Fv/Fm were recorded. Water deficit resulted in 3-4-fold reductions in shoot biomass, root biomass and stomatal conductance along with 1.2-1.4-fold increases in leaf and stem dry matter content and SPAD values. Total dry mass and apparent root length density showed accession by treatment interactions. Accessions DS70622, DS11320 and ILB938/2 shared relatively high values of total dry mass and low values of stomatal conductance under water deficit, but differed in root distribution parameters. In both treatments, DS70622 was characterized by finer roots that were distributed in both depth and width, whereas DS11320 and ILB938/2 produced less densely growing, thicker roots. French accession Mélodie/2 was susceptible to drought in the vegetative phase, in contrast to previous results from the flowering phase, showing the importance of timing of drought stress on the measured response. Syrian accession DS70622 explored the maximum root volume and maintained its dry matter production, with the difference from the other accessions being particularly large in the water-limited treatment, so it is a valuable source of traits for avoiding transient drought.